Influence of the large-scale climate variability on daily rainfall extremes over Argentina - Robledo, Federico Ariel (2016)
A singular value decomposition (SVD) analysis was performed jointly on the daily intensity of extreme rainfall (DIER) over Argentina and sea surface temperature (SST) anomalies from 17.5∘N?90∘S to describe and understand the influence of the large-scale variability of the SSTs on the regional extreme rainfall events for spring summer, autumn and winter. Three main leading modes were identified in agreement with previous works. Mode 1 activity is strongly related to El Niño-Southern Oscillation (ENSO). Warm anomalies in the central-eastern tropical Pacific and western Indian Ocean induce circulation anomalies extended along the South Pacific and the development of a continental-scale circulation gyre in South America promoting moisture convergence, and in turn favouring DIER positive anomalies, in eastern Argentina. The combined influence of SST anomalies in the tropical Atlantic and western tropical Pacific characterizes Mode 2 activity, which induces an anticyclonic (cyclonic) circulation gyre in southeastern South America promoting anomalous moisture convergence (divergence) and thus positive (negative) DIER anomalies in eastern Argentina in spring and fall (summer and winter). Finally, Mode 3 activity is also influenced by SST anomalies in tropical central-eastern Pacific from winter to summer. The associated teleconnections contribute to the development of a cyclonic circulationmainly influencing southeastern SouthAmerica (SESA) circulation to the north of 30∘S from summer to winter, and further south in spring.